Produção cerâmica no início do Neolítico em Portugal: dados recentes sobre os VI e V milénios A.C. - Carvalho, António Faustino (2020)
A characterisation of the earliest pottery productions in Neolithic Portugal (6th millennium BC) was published in the pages of this journal a few years ago. However, three aspects have been receiving further attention by current research and are discussed here: 1) the relation between Cardial and Boquique-decorated potteries, in which the former are clearly more ancient i f a critical evaluation of the available chrono-stratigraphic evidence is carried out; 2) new finds of so-called "symbolic pottery", which includes abundant evidence for anthropomorphic and zoomorphic depictions along with more scarce examples of plant and solar representations; and 3) petrographic and chemical analyses of ceramics and clays, both pointing to the conclusion that Cardial and corded pots were being transported through long-distance, maritime travels. Some sites currently under analyses may provide in the near future new insights into those research topics.